2014
DOI: 10.1074/jbc.m113.508143
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Cardiac Phosphatidylinositol 3-Kinase (PI3K)/Akt Signaling by Apoptosis Regulator through Modulating IAP Expression (ARIA) Regulates Cardiomyocyte Death during Doxorubicin-induced Cardiomyopathy

Abstract: Background:The PI3K/Akt signaling regulates many aspects of cardiomyocyte homeostasis. Results: ARIA regulates cardiac PI3K/Akt signaling and modifies cardiomyocyte death and stress-induced cardiac dysfunction. Conclusion: ARIA is a novel factor involved in the regulation of cardiac PI3K/Akt signals. Significance: ARIA-mediated manipulation of cardiac PI3K/Akt signaling is an intriguing therapeutic target to treat cardiac dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 44 publications
4
41
0
Order By: Relevance
“…In particular, enhancement of MMP2 in cardiomyocytes in response to DOX has been identified as redox‐dependent (Spallarossa et al, 2006; Mukhopadhyay et al, 2009; Bartekova et al, 2015). Other significant changes induced by DOX and mediated by Nox2 indicated up‐regulation of gene expression and included increased phosphoinositide‐dependent protein kinase‐1, which is an important mediator of PI3K signalling, promoting cardiomyocyte survival via the PI3K‐Akt pathway (An et al, 2013; Kitamura et al, 2014). Similarly, DOX‐induced up‐regulation of HSP binding protein 1, which is implicated in maintaining redox homeostasis by upholding glutathione levels (Christians et al, 2012), may signify an attempt to promote survival by counteracting increased ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, enhancement of MMP2 in cardiomyocytes in response to DOX has been identified as redox‐dependent (Spallarossa et al, 2006; Mukhopadhyay et al, 2009; Bartekova et al, 2015). Other significant changes induced by DOX and mediated by Nox2 indicated up‐regulation of gene expression and included increased phosphoinositide‐dependent protein kinase‐1, which is an important mediator of PI3K signalling, promoting cardiomyocyte survival via the PI3K‐Akt pathway (An et al, 2013; Kitamura et al, 2014). Similarly, DOX‐induced up‐regulation of HSP binding protein 1, which is implicated in maintaining redox homeostasis by upholding glutathione levels (Christians et al, 2012), may signify an attempt to promote survival by counteracting increased ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Medial wall thickness was also determined as previously described (18). Wheat germ agglutinin (WGA) staining was performed as previously described (13).…”
Section: Mice and Hypoxia Experiments In Vivomentioning
confidence: 99%
“…Moreover, we have previously demonstrated that loss of ARIA enhanced insulin sensitivity, as well as protected mice from diet-induced obesity and metabolic disorders by modulating endothelial insulin signaling and adipose tissue angiogenesis (27). Additionally, genetic loss of ARIA ameliorated doxorubicin-induced cardiomyopathy (21). These findings strongly suggest that ARIA is a unique and distinctive target for the prevention and/or treatment of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 64%
“…ARIA is highly expressed in endothelial cells; therefore, loss of ARIA substantially enhanced angiogenesis by accelerating endothelial PI3K/Akt signaling. Moreover, we found a significant role of ARIA in the fine-tuning of PI3K/Akt signaling in cardiomyocytes (21). ARIA deficiency protects the heart from doxorubicin-induced cardiac dysfunction by reducing cardiomyocyte death due to enhanced cardiac PI3K/Akt signaling.…”
mentioning
confidence: 76%
See 1 more Smart Citation